BACHD Mice Recapitulate the Striatal Parvalbuminergic Interneuron Loss Found in Huntington’s Disease - Rallapalle, Vyshnavi; King, Annesha C.; Gray, Michelle (Frontiers in Neuroanatomy, 2021)
Huntington’s disease (HD) is a dominantly inherited, adult-onset neurodegenerative disease characterized by motor, psychiatric and cognitive abnormalities. Neurodegeneration is prominently observed in the striatum where GABAergic medium spiny neurons (MSN) are the most affected neuronal population. Interestingly, recent reports of pathological changes in HD patient striatal tissue have identified a significant reduction in the number of parvalbumin expressing interneurons which becomes more robust in tissues of higher disease grade. Analysis of other interneuron populations, including somatostatin, calretinin, and cholinergic, did not reveal significant neurodegeneration. Electrophysiological experiments in BACHD mice have identified significant changes in the properties of parvalbumin and somatostatin expressing interneurons in the striatum. Furthermore, their interactions with MSNs are altered as the mHTT expressing mouse models age with increased input onto MSNs from striatal somatostatin and parvalbumin expressing neurons. In order to determine whether BACHD mice recapitulate the alterations in striatal interneuron number as observed in HD patients, we analyzed the number of striatal parvalbumin, somatostatin, calretinin, and choline acetyltransferase positive cells in symptomatic 12-14 month-old mice by immunofluorescent labeling. We observed a significant decrease in the number of parvalbumin expressing interneurons as well as a decrease in the area and perimeter of these cells. No significant changes were observed for somatostatin, calretinin, or cholinergic interneuron numbers while a significant decrease was observed for the area of cholinergic interneurons. Thus, the BACHD mice recapitulate the degenerative phenotype observed in the parvalbumin interneurons in HD patient striata without affecting the number of other interneuron populations in the striatum.